Efficient peroxymonosulfate activation by biochar-based nanohybrids for the degradation of pharmaceutical and personal care products in aquatic environments. (January 2023) - Liu, Tong; Cui, Kangping; Li, Chen-Xuan; Chen, Yihan; Wang, Qi; Yuan, Xinrui; Chen, Yawen; Liu, Jun; Zhang, Qiang
Abstract: Recently, pharmaceutical and personal care products (PPCPs) have been of wide concern due to their ecological toxicity, persistence, and ubiquity in aquatic environments. Peroxymonosulfate-based advanced oxidation processes (PMS-AOPs) have shown great potential for eliminating PPCPs due to their superior oxidation ability and adaptability. Biochar-based nanohybrids have been employed as emerging catalysts for peroxymonosulfate (PMS) activation. Until now, few researchers have summarized PMS activation by biochar-based catalysts for PPCPs removal. In this review, the types, sources, fates, and ecological toxicities of PPCPs were first summarized. Furthermore, various preparation and modification methods of biochar-based catalysts were systematically introduced. Importantly, the application of activating PMS with biochar-based multifunctional nanocomposites for eliminating PPCPs was reviewed. The influencing factors, such as catalysts dosage, PMS dosage, solution pH, temperature, anions, natural organic matters (NOMs), and pollutants concentration were broadly discussed. Biochar-based catalysts can act as electron donors, electron acceptors, and electron shuttles to activate PMS for the removal of PPCPs through radical pathways or/and non-radical pathways. The degradation mechanisms of PPCPs are correlated with persistent free radicals (PFRs), metal species, defective sites, graphitized degree, functional groups, electronic attributes, and the hybridization modes of biochar-based catalysts. Finally, the current problems and further research directions on the industrial application of biochar-based nanocomposites were proposed. This study provides some enlightenment for the efficient removal of PPCPs with biochar-based catalysts in PMS-AOPs. Graphical abstract: Image 1 Highlights: The types, sources, fates and ecological toxicities of PPCPs were summarized. Biochar had superior catalytic properties by various modification methods. PPCPs could be efficiently degraded in biochar-based catalysts/PMS systems. Future development of biochar-based catalysts in AOPs was prospected.